The Nitrogen Learing In Applicated Peatlands Low Slow Npk Fertilizers And Fertilizers And Their Effect On Growing Of Sweet Maize (Zea Mays Sacchararata Sturt) - Rudi Yanto Sirait; Wawan Wawan; Adiwirman Adiwirman (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2021)
Utilization of peat as agricultural land faced the problem of low soil fertility. Low soil fertility made nitrogen being leached easily. One solution to overcome Nitrogen leaching and efficiency fertilizer raising used dolomite and slow decompose fertilizers. This study aims to determine the effect of dolomite on Nitrogen element leaching in several types of NPK slow decompose applied for corn cultivation in peatland and determine the best dolomite dosage and NPK slow decompose with minimum Nitrogen leaching to optimum sweet corn plant growth in peatland. This research was conducted from August to October 2018 in the Experimental Garden Technical Implementation Unit and Soil Laboratory, Faculty of Agriculture, University of Riau. This research used experimentally and completely randomized design (CRD) factorial. The first factor is dolomite which consists of 4 levels (0 tons.ha-1, 2.5 tons.ha-1, 5 tons.ha-1, dan 7.5 tons.ha-1). The second is NPK slow decompose which consists of 4 levels (NPK single pearl, NPK 13: 6: 27: 4 + 0,65B Mahkota B, NPK 13: 6: 27: 4 + 0,65B Compound Plus Hi-Kay and NPK 13: 8: 27: 4 MgO Ztick). The results showed the administration of dolomite 23.55 g per tube and NPK slow decomposed could reduce Nitrogen leaching, improve physiology and growth of sweet corn plants. Provision of interaction between dolomite 5 ton.ha-1 with NPK slow decomposition (30.25 N, 3.72 P, 12.56 g per tube) produces the best interaction that can reduce the proportion of Nitrogen leaching and it can affects the increasing of plant growth.